Évolution de la relation rang-taille dans le système urbain québécois entre 1871 et 1976 - Brunet, Yves (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractAn analysis of 10 variables caracterising the distribution of the Québec's cities size, permitted identification of 3 distinct phases of evolution of the urban system since 1871. Primatial growth reached a maximum in the 1920s and was followed by a transition-maturation period where, around 1956, the number of centers stabilized at 60. Lognormality was then at a maximum. Since that peak, the metropolisation process induced a new spell of primatial growth.The Quebec urban structure is still markedly unbalanced, the transition from primacy to lognormality is still going on. Its longing could be explained by the fact that in Quebec the "center-periphery" spatial dualism is doubled with an ethno-linguistic dualism. Without the french-english opposition one can think that the transition period would have resolved rapidly with the development of non-metropolitan industrial complexes.